Readiness to Implement the Digital Village Program: A Case Study: Waru Village, Waru Sub-district, Sidoarjo Regency - Rohmadiani, Linda Dwi; Ramadhani, Galih Andika (Formosa Journal of Science and Technology, 2024)
The readiness of the Waru Village community based on the analysis results is at the Confirmation/Expansion stage (Confirmation Provider) which shows that the Waru Village community is ready to implement the digital village program and actively participate, by utilizing resources and the role of leaders. This study aims to determine the level of readiness of the Waru Village community in implementing the digital village program, this study uses the Community Readiness Model (CRM) analysis technique through a questionnaire with weighting (scoring) on ​​each variable consisting of community efforts, community knowledge of efforts, leadership, community climate, community knowledge of issues, and resources related to issues. The results of the study showed that the level of readiness of the Waru Village community was at level 8 with a score of 78. The factors that influence the readiness of the Waru Village community are physical factors with a score of 0.830. The physical factors referred to are good physical and mental health as a basis for community empowerment to implement the digital village program. In implementing the digital village program in Waru Village, it can improve the local economy towards markets and public services, increase community access to public services through the Simpeldesa application, and develop digital infrastructure.